Comparison of four molecular approaches to identify Candida parapsilosis complex species - Barbedo, Leonardo Silva (2017)
Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Laboratório de Micologia. Rio de Janeiro, RJ, Brasil.